Individual psychological prerequisites for self-realization of IT specialists - Kudinov, Sergey I.; Belyaeva, Evgeniya N. (Saratov State University, 2023)
The relevance of the study is due to the poor development of the problem of professional self-realization of IT specialists. The specifi city of the professional activity of this category of employees imposes special requirements on their individual psychological characteristics, which ensure the success of self-realization of specialists engaged in information and computer activities. Purpose: to identify the specifi cs of self-realization of IT professionals with diff erent individual typological features. Hypothesis: a set of certain individual-personal characteristics forms diff erent individual-psychological types of IT specialists, which act as a prerequisite for professional self-realization of the subject of this profession. Participants: employees of leading Russian IT companies (Moscow) (N = 154) – 42 women and 112 men aged 22 to 44 (average age 32.09±5.71). Methods (tools). To study the individual and personal characteristics of IT specialists, the following were involved: “IndividualTypological Questionnaire – ITQ” (L. N. Sobchik), “Personality Questionnaire – EPI” (G. Eysenck), questionnaire “Strategies for Coping with Stressful Situations - SACS” (S. Hobfall). When identifying the specifi cs of self-realization of IT specialists with diff erent individual typological features, the “Multidimensional Questionnaire of Personal Self-Realization” (S. I. Kudinov) was used. Results: it was found that such characteristics as “anxiety”, “sthenicity”, “extraversion” and “lability” are leading ones in the structure of individual traits of IT-specialists. The dominant coping strategies of IT-specialists are “entering into social contact”, “search for social support”, “cautious actions”. As a result of cluster analysis, three types of individuality of IT-specialists were identifi ed and characterized: “introverted-confi dent”, “extroverted-active”, “extraverted-prosocial”. According to the results of a comparative analysis the data on the confi guration of the types of self-realization in each cluster are presented. It has been established that specialists of the “introverted-confi dent” type demonstrate the highest rates in all types of self-realization: personal, social and professional. This allows us to consider this type of personality as the main predictor of eff ective self-realization of IT specialist’s personality. Main conclusions: 1) there is a certain specifi city in the manifestation of self-realization of IT specialists with diff erent individual typological features; 2) the practical signifi cance of the study is emphasized in the context of psychological support for the professional self-realization of IT specialists, taking into account their personal characteristics.